Effect of polypyrrole nanostructures on the anti-corrosion performance of polypyrrole/polyvinyl butyral/carbon black coatings. Issue 19 (2nd October 2022) - Hao, Lu; Zhu, Kaiming; Yu, Demei
Abstract: Polypyrrole nanoparticles (PPy NPs), nanorods (NRs), and nanotubes (NTs) are prepared by a green chemical oxidation method using H2 O2 as an oxidant under UV irradiation. The anti-corrosion coatings are prepared by hybridizing different nanostructured PPy, polyvinyl butyral, and carbon black for protecting zinc metal. The effect of the content of PPy on corrosion-resistant of the coatings is investigated, and the influence of the PPy nanostructures on the anti-corrosion performance of the coatings is also investigated by the electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization curves. It is found that the composite coatings with nano-PPy have obvious anticorrosive performance, and the corrosion resistance is evidently enhanced with the increase of the content of PPy nanostructures. It is further found that the coatings containing PPy NPs have the best corrosion resistance. The possible anti-corrosion mechanism of the anti-corrosion coatings is proposed.